G protein‐coupled receptor 119 agonist DS‐8500a effects on pancreatic β‐cells in Japanese type 2 diabetes mellitus patients. Issue 1 (4th May 2018) - Watada, Hirotaka; Shiramoto, Masanari; Irie, Shin; Terauchi, Yasuo; Yamada, Yuichiro; Shiosakai, Kazuhito; Myobatake, Yusuke; Taguchi, Takashi
Abstract: Aims/Introduction: Pancreatic β‐cell dysfunction contributes to type 2 diabetes mellitus progression. Drugs that improve insulin secretion might be a valuable treatment approach. The present study aimed to evaluate the effect of the G protein‐coupled receptor 119 agonist DS‐8500a on insulin secretory capacity in Japanese type 2 diabetes mellitus patients. Materials and Methods: This single‐center, 4‐week, randomized, double‐blind, cross‐over study enrolled 21 Japanese drug‐naïve type 2 diabetes mellitus patients aged ≥20 years with glycated hemoglobin ≥7.0 and <9.0% (NCT02669732, JapicCTI 163126). Patients received 75 mg of DS‐8500a or a placebo orally daily for 4 weeks in a random order. A combined euglycemic‐hyperinsulinemic and hyperglycemic clamp test was carried out to assess insulin secretion and insulin sensitivity before and after each 4‐week treatment period. Primary end‐points were first‐phase insulin secretion (insulin area under the curve [AUC]180–190 min and C‐peptide AUC180–190 min during the clamp test) and second‐phase insulin secretion (insulin AUC190–300 min and C‐peptide AUC190–300 min ). Insulin sensitivity ( M and M / I values), disposition index and changes in lipid profile were also assessed. Results: DS‐8500a significantly increased first‐ and second‐phase insulin AUC ( P = 0.0011, P = 0.0112) and C‐peptide AUC ( P = 0.0012, P < 0.0001) compared with the placebo. At day 28, M and M / I values were comparable with those of the placebo, whereas the disposition index for insulin and C‐peptide was significantly increased ( P = 0.0108, P = 0.0002). Total cholesterol, low‐density lipoprotein cholesterol and triglyceride concentrations were significantly reduced, and high‐density lipoprotein cholesterol concentrations were significantly increased compared with the placebo. No significant treatment‐emergent adverse events occurred. Conclusion: DS‐8500a enhanced insulin secretory capacity, but not insulin sensitivity. Abstract : This randomized, double‐blind, placebo‐controlled, 2 × 2 crossover study was designed to evaluate the effect of 28‐day oral administration of the G protein‐coupled receptor 119 agonist DS‐8500a on insulin secretory capacity in Japanese T2DM patients. DS‐8500a significantly increased first‐ and second‐phase insulin AUC ( P = 0.0011, P = 0.0112) and C‐peptide AUC ( P = 0.0012, P < 0.0001) compared with placebo. DS‐8500a enhanced insulin secretory capacity but not insulin sensitivity in Japanese T2DM patients during the study period.